Development of Ultra-High Performance Concrete against Blasts: From Materials to Structures - Wu, C.; Li, Jun; Su, Y. (2018)
© 2018 Elsevier Ltd. All rights reserved. Development of Ultra-High Performance Concrete against Blasts: From Materials to Structures presents a detailed overview of UHPC development and its related applications in an era of rising terrorism around the world. Chapters present case studies on the novel development of the new generation of UHPC with nano additives. Field blast test results on reinforced concrete columns made with UHPC and UHPC filled double-skin tubes columns are also presented and compiled, as is the residual load-carrying capacities of blast-damaged structural members and the exceptional performance of novel UHPC materials that illustrate its potential in protective structural design. As a notable representative, ultra-high performance concrete (UHPC) has now been widely investigated by government agencies and universities. UHPC inherits many positive aspects of ultra-high strength concrete (UHSC) and is equipped with improved ductility as a result of fiber addition. These features make it an ideal construction material for bridge decks, storage halls, thin-wall shell structures, and other infrastructure because of its protective properties against seismic, impact and blast loads.